THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ON STUDENTS’ READING COMPREHENSION - Mafruhah, Anisatul (Tanfidziya: Journal of Arabic Education, 2025)
Reading has been became one of the current issues in language learning. The EFL learner is still get difficulties to comprehend the text. In this case, some of method is needed to improve their reading comprehension. The aim of this research is to find out the effect of student team achievement division (STAD) on students’ reading comprehension. Reading is a base of knowledge. Students should be able to comprehend  the text. A such method also needed to improve their reading comprehension. Reading comprehension means an interactive process between reader and the text, in that the reader is required to fit clues provided the text. Since the CL method turns out to be a valuable tool to help students in learning comprehension strategies, the researcher chose STAD in teaching reading comprehension. This research is experimental research which is done with two group of classes. The experimental group and the control group which is each group consists of 30 students. Sample of this research is choosen by intact classes technique. The experimental group was taught by using STAD, while the control group was taught by using conventional instruction. This research is quasi experimental research which the data is taken from pos test. The result of this study indicates that the students who taught by using STAD have better literal and inferential reading comprehension than the students who taught by using conventional instruction